PROCEDURES FOR MEASURING OS FEMORALIS USING ORTHOROENTGENOGRAPHIC METHOD: TATA LAKSANA PENGUKURAN OS FEMORALIS DENGAN METODE ORTHOROENTGENOGRAFI - CICILLIA - ARTITIN (JURNAL TERAS KESEHATAN, 2021)
The Femur the longest bone of the body. The bone is a pipe bone and has a stem and two ends, with an indication of examination for the presence of congenital abnormalities in the bone, the occurrence of a fracture or fissure and several other cases sich as spiral fractures that cause shortening of overlapping fragment, or communal fracture (broken into pieces) an resulting in changes in size, shape and length of the bone. Orthorontgenografi method is a method that provides certainty in measuring the length of the bone in moral detail, accurate and specifications on the bone to be measured. The purpose of this study is know the measurement results os femur by using orthorontgenografi method. The type of research is using research quantitative with the experimental method is being done to get results conclusion, place and time study published in May 2019 at the Ropanosuri Padang Special Surgical Hospital. This study was conducted on one male patient, 18 years old and 172 cm tall with clinical post orif on the femur. The results of the study of measurement of femoral bone with orthoroentgenography method were obtained at length in the medial part of the femur is 28 cm, in the distal part of the femur is 11.9 cm, in the proximal part of the femur is 4,6 cm. The overall results of the measurements obtained 44.5 cm. From the discussion above, it can be seen that the method of orthoroentgenography is a method that can accurately prove the correct and accurate measurement of the femur on the examination of the femoral bone. Keywords : Os Femoralis, Radiographic, Orthoroentgenografi Method